Software Support for the Higher Mathematics Course at the Technical University - Oleksii Viktorovych Bogdanov; Yurii Pavlovych Butsenko; Olena Ivanivna Balina; Iryna Srhiivna Bezklubenko (Mìkrosistemi, Elektronìka ta Akustika)
The paper addresses the challenges of training modern engineers in mathematical disciplines. It emphasizes the need for graduates to possess theoretical knowledge and be capable of using modern software solutions for efficient mathematical calculations. The article discusses the importance of incorporating mathematical software into higher education to enhance the teaching of mathematical disciplines. Explores the potential benefits and challenges of using mathematical software in the learning process, such as the need for coordination among teachers and the importance of familiarizing students with the interfaces of mathematical packages. The paper recommends using specific mathematical software packages, such as Scilab, for scientific and engineering calculations. It also highlights the necessity of guiding students in understanding the practical applications of mathematical software in solving complex mathematical problems. Furthermore, the paper addresses the issue of preventing students from inappropriately using online calculators for tasks, emphasizing the importance of mastering theoretical foundations before utilizing mathematical software packages. The paper generally advocates for a balanced approach that incorporates both traditional theoretical exposition and practical application of mathematical programs in higher education to promote effective teaching and learning of mathematical disciplines.